(3EceGd JgPjH GdceGd aj CSeGA GdQLGds - (3oenZrdWGj Hf nbpdjL Hf YHO Gddg GdHcLQj GdeUQj GdMcQj GdMfaj, CHh YHO Gddg, YdGA GdOjf , J (B762 (3g` s; (3GdMGaX GdeRj , jhSa Hf YHO GdQMef Hf jhSa LeGd GdOjf GdRcj CHh eMeO GdbVGYj GdcdHj, LeGd GdOjf CHh GdMLGL GdMGaX GdeRj,J (B742 (3g` s
(3ChdgG (B:s
(3eMeO Hf YHO Gdedc Hf RfLhf GdHZOGOi s
(3BNQgG (B:s
(3HjMi Hf YKeGf Hf UGdM Hf UahGf BNQ GdLRA GdKGfi YTQ ef cJGH GceGd JgPjH GdceGd s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B308s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B30 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs